The Power of Adapted Sports, Changing Attitudes in Higher Education: An Exploratory Study - Archambault, MaryJo; Searcy, Yan Dominic (Palaestra, 2018)
A wheelchair basketball showcase was hosted at a state university in New England. Student surveys revealed that the event had a positive effect on students’ views of both individuals with disabilities and adapted sports. Using Allport’s (1954) contact theory as a lens, the author demonstrates how the event met the four positive features that Allport believed should be present in order to reduce negative feelings toward another group: (a) equal status between the groups, (b) common goals, (c) intergroup cooperation and (d) the support of authorities. This exploratory study argues that adapted sports can be an effective method to positively impact stereotypical views of people with disabilities.Subscribe to PALAESTRA
Keywords: Adaptive sports; changing attitudes; contact theory; dept.hhs; dept.rec; higher education; peer-reviewed; ⛔ No DOI found

Historical persecution reaction complex: exploring a link between racial identity and poor leadership outcomes - Searcy, Yan Dominic; Hines, Resche D. (Journal of Black Studies, 2017)
This original study examines the reluctance of oppressed populations to publicly criticize the recognized performance shortcomings of leaders who are members of their identity group. Using critical race theory (CRT), this article utilizes three case examples of Black American leadership that present evidence of what the authors identify as Historical Persecution Reaction Complex (HPRC). HPRC describes four elemental arguments reflecting an oppressed identity group's attempt to protect itself from perceived further social marginalization, limit the exacerbation of oppression, and to preserve the identity group's leadership gains in the larger society by supporting leadership despite recognized shortcomings in the leadership. Although asserting HPRC operates as a functional reaction to oppression by serving both as an act of cohesion and resistance to oppressive structures, the authors suggest that HPRC is paradoxically detrimental to oppressed identity groups due to maintaining substandard leadership.
Keywords: Black identity; antiracism; dept.hhs; leadership; oppression; racial identity